Gender Diversity Leadership and ESG Performance : The Influence of Women on Boards and in Management - Sandretto, Davide; Rizzi, Alessandro; Esposito, Gabriella (John Wiley & Sons, 2025)
In recent years, there has been a growing interest among companies and regulatory bodies in adhering to environmental, social, and governance (ESG) standards, alongside an increased involvement of women in organizational decision-making processes. In this study, we investigate the potential advantages of female representation in leadership positions on the firms' ESG performance. Using a dataset comprising 2646 public companies across Europe, America, and Asia from 2013 to 2022, we find a significant positive correlation between gender diversity and companies' sustainability performance. However, a granular analysis of the three pillars (environment, social, and governance) reveals nuanced results. Specifically, board gender diversity is only positively related to the governance score, but females in managerial positions are associated with higher social scores. These findings consistently hold after conducting a series of robustness tests to address endogeneity concerns. Our study provides practical implications for policymakers and practitioners, advocating for greater engagement of women in leadership roles.
Keywords: ESG performance; gender diversity; women managers; boards of directors; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|